The radio station - Keith, Michael C. (Elsevier/Focal Press, 2004)
The Radio Station explains how radio stations operate from the inside-out, from technology to operations, and from sales to syndication. It offers an overview of how government regulations effect radio stations today, how radio stations have adapted to new communications technologies, and the basics of who does what at a radio station. Now in its sixth edition, it has received much acclaim by radio educators and practitioners from around the United States. This new edition features a cover to cover update, including new material on satellite radio, the shift from analog to digital technologies, Internet use,and most recent regulatory changes in the industry.